School education and adolescents infractional acts authors marginalization - JULIO CESAR FRANCISCO
This article aims identify the relation between the marginalization process by the attended people for socioeducational measure and the scholar education. This investigation deals with a problem of extreme relevance and that impact in a poor population that is socially and culturally marginalized: the increasing involvement of adolescents in infraction acts. For the production of the article, it was used, besides the actual legislation, some other theoretical references: Silva (2003); Becker (1997), Zaluar (1994), Merton (1967), Goffmam (1981) e Veronese & Lima (2009), that contributed with the conception of the marginalization process. Still, Dermeval Saviani, in the book School and Democracy (1983), is taken as an author who shows how the organization and operation of the school interfere in this matter. Finally, I present an educational proposal to be developed in socio-educative measure, articulated to the Saviani's historical critique pedagogy and Paulo Freire's pedagogy, which suggests an educational act that allows the unveiling of the oppressive conditions for them to act and transform.